(untitled) (TAMADDUN NURI JURNALI, 2025)
In the article, proverbs and sayings from Mahmud Kashgari’s work «Devoni lug’atit turk» were analyzed as units with a somatic component used in human body parts. The article reveals Turkic words and their meanings, the presentation of somatic proverbs and sayings in the Karakalpak language, and their meanings in literary language.